Konstruksi Teologis dalam Hadih Maja - Lukman Hakim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Hadih Maja is an oral literature is the source of value in the lives of the people of Aceh. The content itself hadih maja has a diverse range of values such as the value of law, education, philosophy, ethics and theology. Lately hadih maja is oriented in the realm of law and social issues alone. It makes some of the content of the hadih maja as neglected as the theological side. This paper examines some of the central issues in the study of such concepts qadha kalam and Qadar, rational reasoning and work ethic. In problem qadha and levels found construction theological built in Acehnese society is the existence of an understanding of kalam very balanced between the recognition of the absoluteness of God and human freedom in realizing his actions. In the field of rational reasoning, always taught the use of the maximum reasonable minds before doing an action. Intellect is positioned as a tool to be able to measure the goodness and badness of a deed. While the work ethic has always taught about the spirit and optimism in life. This is the picture that proclaimed theological learning in hadih maja. This of course is a decent value in the lives of the Acehnese appreciated